Efficacy of Adalimumab in Korean Patients with Crohn's Disease - Sohn, Il Woong; Kim, Sung Tae; Kim, Bun; Lee, Hyun Jung; Park, Soo Jung; Hong, Sung Pil; Kim, Tae Il; Kim, Won Ho; Cheon, Jae Hee (Gut and liver, 2016)
Adalimumab is effective for both remission induction and the maintenance of Crohn's disease (CD) in Western countries. We evaluated the efficacy of adalimumab in the conventional step-up treatment approach for CD in Korea. We retrospectively reviewed 62 patients with CD who were treated with adalimumab. Their Crohn's disease activity index (CDAI) was measured at weeks 4, 8, and 52. Clinical remission was defined as a CDAI score <150. Induction and maintenance outcomes were analyzed. Forty-one patients (66.1%) achieved a reduction of 70 CDAI points at week 8. Among them, 28 (45.2%) achieved clinical remission at week 8, 20 (32.3%) maintained remission at week 52. The absence of prior anti-tumor necrosis factor (TNF) therapy and Montreal classification L1 at baseline predicted clinical remission at week 8 in the multivariate logistic regression analysis. In the Cox proportional hazards model, the hazard ratio for the secondary loss of response during maintenance therapy after clinical remission induction was significantly higher in patients who showed initial mild CDAI severity or Montreal classification A3. In our study, anti-TNF therapy-naive and Montreal classification L1 were associated with adalimumab efficacy as induction therapy in CD. Further studies are warranted to determine the prognostic factors for the long-term response after adalimumab therapy.